Conidial production, sporulation period and extension of lesion of Helminthosporium sativum on flag leaves of wheat - Mehta, Y. R. (Pesquisa Agropecuaria Brasileira, 2014)
Studies were carried on conidial production sporulation period and lesion extension of twelve races of Helminthosporium sativum on flag leaves of fourteen wheat cultivars. Cumulative total conidial production varied from zero to 6,335 conidia and the sporulation period varied between zero and 30 days depending on the race and the cultivar under study. The peak of sporulation varied between 23 and 36 days after inoculation but in most of the cases it was reached on the 29th day of inoculation. The maximum final lesion size was 4.4 cm2 and the maximum percentage of leaf area infected by a single lesion was 22.7. The lesion extension in most of the cases was markedly enhanced during the period of 22 to 32 days of inoculation, which was correlated with the drastic increase in conidial production during the same period reaching the peak on the 29th day. In general, the components of partial resistance, like conidial production, sporulation period and the rate of lesion extension acted independently. The rate of lesion extension and final lesion size ware considered to be the desirable parameters of partial resistance. Some of the best sources of partial resistance were the cultivars BH 1146, LD 7831 and PAT 7219.